2019
DOI: 10.1007/s00520-019-05053-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy intravenously in children with cancer at home, the nurse practitioner makes it possible!

Abstract: Background Currently the entire treatment of a child with cancer is carried out in a specialized hospital. It would be ideal to conduct part of the treatment at home. This can only be done with adequately trained personnel. In the Netherlands, specialized pediatric oncology home care nurse practitioners have been trained to deliver this kind of care. Therefore, a pilot study was conducted to administer intravenous chemotherapy at home. Purpose This study aimed to safely administer chemotherapy intravenously (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
(12 reference statements)
0
12
0
5
Order By: Relevance
“…In addition, parents can often be financially affected by hospital stays [ 5 , 6 ] and home care can strengthen family life without negatively impacting on the family’s finances due to, for example, travel costs [ 5 ]. Children have also reported advantages with conducting cancer treatment at home [ 7 ]. Consequently, hospital-based home care contributes to symptom control for children and increases quality of life for families [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, parents can often be financially affected by hospital stays [ 5 , 6 ] and home care can strengthen family life without negatively impacting on the family’s finances due to, for example, travel costs [ 5 ]. Children have also reported advantages with conducting cancer treatment at home [ 7 ]. Consequently, hospital-based home care contributes to symptom control for children and increases quality of life for families [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…- Cancer (n = 22; 34.4%): Twelve (54.5%) home care services were designed for patients with solid tumors, 25-38 while the rest (n = 10; 45.5%) were aimed at patients with lymphoproliferative disorders (leukemia, multiple myeloma, and lymphoma). 39-48…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (25.8%) aimed at evaluating the impact of home care interventions on HRQoL. 26,31,37,43,46,47,74,78 The questionnaires used to assess HRQoL were generic: the EuroQol 5-Dimensional Scale (EQ-5D) or the Short Form-36 Health Survey (SF-36); 26,31,78 disease-specific -the Lung Cancer Symptom Scale (LCSS)- 26,37,46 and the Mini International Neuropsychiatric Interview (MINI); 74 not specified 47 , and an ad hoc questionnaire adapted from a previous study. 43 The majority demonstrated how the interventions improved HRQoL, however, 3 (37.5%) of them showed that patients’ HRQoL remained unchanged, regardless of whether the patient was at home or with the standard of care.…”
Section: Resultsmentioning
confidence: 99%
“…According to this concept [16], nurse practitioners in rural communities of Japan can assist with medical care on behalf of physicians, thereby helping physicians enhance their work and lifestyle [17,18]. At present, nurse practitioners have been serving in many roles in a variety of medical/healthcare settings, such as prescribing practices [19], chemotherapy [20], and memory assessment services for people with suspected dementia [21]. A recent study in England suggested that nurse practitioners can help achieve equivalent clinical outcomes to general practitioners when performing out-of-hours urgent primary care [22].…”
Section: Discussionmentioning
confidence: 99%